(3GdTaG HJYQja Mbhb GdeUWais - (3GdjMUHj, CHh GdaVd, GdbGVj YjGV, YjGV Hf ehSi Hf YjGV, J(B544(3g`s ((3CMeO SGeMs)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdefaQO HGSeg GdCSei GdeNJU HGdedc GdCYRs
(3BNQgG (B:s
(3hdG jQO OYhI GdbGUOjf hdG jUdM Yed GdeaSOjf hgh MSHfG hfYe Gdhcjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 99s
(3eYLe GdeDdajf(B: 2 / 588s
(3cTa GdXfhf(B: 2 / 1052s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs